HER2 overexpression is a putative diagnostic and prognostic biomarker for late-stage colorectal cancer in North African patients. Issue 1 (1st January 2021) - Abdul Razzaq, Eman A.; Venkatachalam, Thenmozhi; Bajbouj, Khuloud; Rahmani, Mohamed; Mahdami, Amena; Rawat, Surendra; Mansuri, Naziha; Alhashemi, Hussein; Hamoudi, Rifat Akram; Bendardaf, Riyad
ABSTRACT: Aim: Colorectal cancer (CRC) is one of the leading cancers in the world. Even though its mortality and pathophysiology are well documented in the US and the European countries, it is seldom studied in North African population. Recent studies have shown link of HER2 overexpression in oesophageal and gastric cancers. The aim of this study is to assess the HER2 protein and mRNA expression and its correlation with tumor pathogenesis in Libyan CRC patients. Methodology: A total of 17 FFPE tissue blocks were collected from patients with primary CRC. The HER2 protein expression was assessed by immunohistochemistry and the mRNA expression was assessed using qRT-PCR. Survival analysis of the role of HER2 overexpression on rectal adenocarcinoma was carried out on additional 165 patients. Results: From the CRC cohort, adenocarcinoma was found to be more frequent accounting for 88.2%, and 11.8% for mucinous adenocarcinomas. Almost 47% of the cases were positive for HER2 (score ≥ 2+) and about 50% adenocarcinoma cases with tumor grade II were positive for HER2. Moreover, 57.4% adenocarcinoma patients with grade-II tumor had undergone right hemicolectomy. Furthermore, significant correlation (p = 0.03) between the HER2 mRNA expression with the tumor grade was observed. In addition, poor overall all survival was observed with high HER2 expression in rectum adenocarcinoma. Conclusion: To our knowledge, this is the first study that HER2 overexpression correlates with more aggressive colorectal cancer in North African population. Our study shows that HER2 overexpression associates with right colon surgeries. Also, the correlation of mRNA and protein expression could warrant the implementation of a nationwide screening program for HER2 positivity in CRC patients. Taken together, stratifying patients according to HER2 expression can help in the diagnosis and prognosis of CRC patients from North African origin.